Physiological aspects of fluid and electrolyte balance - Lobo, Dileep N (2003)
The intake of water and electrolytes is inseparable from feeding by natural or artificial means and careful attention to salt and water balance is a vital component of perioperative care and of nutritional support. Nutritional support with water and sodium restriction in post-intensive care patients with oedema, dilutional hypoalbuminaemia and fluid excess of 10 L, cleared oedema over 7-10 days, with a 1 g/L rise in serum albumin for every kg loss in weight. Return of gastrointestinal function was also observed. Accordingly, 20 patients, undergoing colonic surgery, were randomised to receive standard (>3 L water and 154 mmol sodium/day) or restricted postoperative fluids (<2 L water and 77 mmol sodium/day). Solid (72.5 vs 175 min) and liquid phase (73.5 vs 110 min) gastric emptying times were significantly longer in the standard group on the 4th postoperative day and associated with a three day longer hospital stay. In volunteers receiving 2 L of 0.9% saline and 5% dextrose infusions, on separate occasions over one hour, haematocrit and serum albumin concentration fell, mainly due to dilution. While dextrose was rapidly excreted, two-thirds of the saline was retained after 6 h. Following 1 L infusions, plasma renin and angiotensin concentrations decreased more after saline than dextrose (P<0.04). Responses of aldosterone, atrial natriuretic peptide and vasopressin were not significantly different. Comparing 2 L infusions of saline and Hartmann's solution, volunteers excreted more water (median 1000 vs 450 mL) and sodium (122 vs 73 mmol) after Hartmann's. Hyperchloraemia and reduced bicarbonate were noted after saline alone. Whereas fluctuations in water balance are dealt with efficiently through osmoreceptors and vasopressin, and sodium deficiency by volume receptors and the renin angiotensin aldosterone system, the mechanism for dealing with sodium and chloride excess appears relatively inefficient. Natriuretic peptide responds to volume expansion rather than sodium gain.